Population pharmacokinetics of extended‐release levetiracetam in epileptic dogs when administered alone, with phenobarbital or zonisamide. (20th September 2018) - Muñana, Karen R.; Otamendi, Arturo J.; Nettifee, Julie A.; Papich, Mark G.
Abstract : Background: Extended‐release levetiracetam (LEV‐XR) has gained acceptance as an antiepileptic drug in dogs. No studies have evaluated its disposition in dogs with epilepsy. Hypothesis/Objectives: To evaluate the pharmacokinetics of LEV‐XR in epileptic dogs when administered alone or with phenobarbital or zonisamide. Animals: Eighteen client‐owned dogs on steady‐state maintenance treatment with LEV‐XR (Group L, n = 6), LEV‐XR and phenobarbital (Group LP, n = 6), or LEV‐XR and zonisamide (Group LZ, n = 6). Methods: Pharmacokinetic study. Blood samples were collected at 0, 2, 4, 8, and 12 hours after LEV‐XR was administered with food. Plasma LEV concentrations were determined by high‐pressure liquid chromatography. A population pharmacokinetic approach and nonlinear mixed effects modeling were used to analyze the data. Results: Treatment group accounted for most of the interindividual variation. The LP group had lower C MAX (13.38 μg/mL) compared to the L group (33.01 μg/mL) and LZ group (34.13 μg/mL), lower AUC (134.86 versus 352.95 and 452.76 hours·μg/mL, respectively), and higher CL/F (0.17 versus 0.08 and 0.07 L/kg/hr, respectively). The half‐life that defined the terminal slope of the plasma concentration versus time curve (~5 hours) was similar to values previously reported for healthy dogs. Conclusions and Clinical Importance: Considerable variation exists in the pharmacokinetics of LEV‐XR in dogs with epilepsy being treated with a common dose regimen. Concurrent administration of phenobarbital contributed significantly to the variation. Other factors evaluated, including co‐administration of zonisamide, were not shown to contribute to the variability. Drug monitoring may be beneficial to determine the most appropriate dose of LEV‐XR in individual dogs.